Preparation method of iron disulfide electrostatic spinning self-supporting positive electrode for aqueous battery

The preparation of iron disulfide/nitrogen doped carbon fiber self-supported positive electrodes through electrospinning technology, solving the problems of low energy density and poor structural stability of the positive electrode materials of aqueous zinc ion batteries, achieving excellent rate performance and cycling performance, and improving the mass energy density of the battery.

CN119852299APending Publication Date: 2025-04-18TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510050635.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

Smart Images

  • Figure CN119852299A_ABST
    Figure CN119852299A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron disulfide electrostatic spinning self-supporting positive electrode for an aqueous battery, and belongs to the technical field of batteries. A three-dimensional network carbon fiber composite material is designed and prepared through low-temperature stabilization and high-temperature carbonization by using an electrostatic spinning technology, and nano iron disulfide particles are obtained through in-situ vulcanization on the basis of the material. And finally, preparing the iron disulfide / nitrogen-doped carbon fiber self-supporting positive electrode. According to the preparation method disclosed by the invention, the preparation of the positive electrode self-supporting material with excellent rate capability and cycle performance is realized; the use of a current collector, a binder and a conductive agent is avoided, the mass energy density of the battery is greatly improved, and the battery shows a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a method for preparing a self-supporting positive electrode of iron disulfide electrospun for an aqueous battery. Background Art

[0002] Aqueous batteries are considered to be one of the most promising technologies due to their low cost, environmental friendliness and high safety. They can be used as an effective supplement or even substitute for lithium-ion batteries and sodium-ion batteries in the market, and have great application potential in the field of large-scale energy storage. However, aqueous zinc-ion batteries currently rely mainly on embedded positive electrode materials, such as vanadium-based, manganese-based, Prussian blue, organic materials, etc., but the energy density of the above materials is generally low. Metal sulfides based on the conversion reaction mechanism can achieve high theoretical specific capacity through the transfer of multiple electrons, which can just make up for the disadvantage of insufficient energy density of aqueous zinc-ion batteries.

[0003] Pyrite (FeS2) is considered to be one of the most promising electrode materials due to its high theoretical capacity, abundant resources and low price. However, it has many problems, including:

[0004] 1. Low electronic and ionic conductivity;

[0005] 2. Structural degradation during the cycle;

[0006] 3. Powdering of electrodes and dissolution of polysulfides;

[0007] The above problems will lead to rapid attenuation of battery capacity. At the same time, in the traditional electrode preparation process, the use of binders, conductive agents and current collectors will reduce the mass energy density of the battery itself, which is not conducive to practical application.

[0008] Therefore, it is necessary to provide a method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries to solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing an electrostatically spun self-supporting positive electrode of iron disulfide for aqueous batteries to solve the technical problems existing in the above-mentioned iron disulfide positive electrode materials. The preparation method uses electrostatic spinning technology, and after low-temperature oxidation and high-temperature carbonization, a three-dimensional mesh carbon fiber composite material is designed and prepared, and nano iron disulfide particles are obtained by in-situ sulfurization on the basis of the material. Finally, the prepared iron disulfide / nitrogen-doped carbon fiber self-supporting positive electrode exhibits excellent rate performance and cycle performance. At the same time, since the use of current collectors, binders and conductive agents is avoided, the mass energy density of the battery is greatly improved, showing good application prospects.

[0010] To achieve the above object, the present invention provides a method for preparing an electrostatically spun self-supporting positive electrode of iron disulfide for an aqueous battery, comprising the following steps:

[0011] S1, adding polyacrylonitrile (PAN) and ferric acetate into N, N-dimethylformamide (DMF), stirring evenly until completely dissolved to form a uniform spinning solution;

[0012] S2, transferring the spinning solution into a syringe, applying high voltage between the needle of the syringe and the collector, and spinning the nanofiber membrane in situ on the collector by controlling the injection speed and the rotation speed of the drum;

[0013] S3, after drying the nanofiber membrane, annealing at low temperature in air to stabilize it, dehydrogenation, cyclization and oxidation of polyacrylonitrile (PAN) occur, resulting in the conversion of Fe(AC)2 into Fe2O3, further carbonization of the nanofiber membrane, Fe2O3 into Fe3C, and at the same time, due to the pyrolysis of the additional nitrile group, the carbon content increases, and finally a carbonized fiber membrane rich in pore structure is obtained. The carbonized fiber membrane is a three-dimensional porous material, and this structure greatly improves the electrolyte infiltration degree and active specific surface area;

[0014] S4, the carbonized fiber membrane is subjected to vapor phase vulcanization, and the Fe3C embedded in the nanocarbon fiber reacts with the sulfur-containing atmosphere at high temperature and is in situ converted into FeS2 nanoparticles, which are evenly distributed on the porous three-dimensional carbon fiber skeleton of the carbonized fiber membrane to obtain a nanofiber film loaded with iron disulfide; a high-speed electron and ion transmission channel is constructed, the volume expansion during the reaction process suppresses the structural damage to the positive electrode, and the structural stability of the positive electrode material is improved;

[0015] S5. Cut the nanofiber film loaded with iron disulfide and use it as the positive electrode material of the battery.

[0016] Preferably, the mass ratio of the nanofiber film to the loaded iron disulfide is 1:3-4.

[0017] Preferably, in step S1, the molecular weight of polyacrylonitrile is 150000-200000, the input mass ratio of polyacrylonitrile and ferric acetate is 7:8, the mass volume ratio of ferric acetate to dimethylformamide is 0.8g:8-10ml, and the stirring time is 12h.

[0018] Preferably, in step S2, the diameter of the syringe needle is 19-21G, the distance between the syringe needle and the collector is fixed at 18 cm, the negative high voltage and the positive high voltage are -2 and 16 kV respectively, the injection speed is 1 ml / h, the drum speed is 200 r / min, and the spinning environment humidity is controlled at 25-35%.

[0019] Preferably, in step S3, the stable temperature of low-temperature annealing in air is 280°C, the heating rate is 2°C / min, and the holding time is 2h.

[0020] Preferably, in step S3, the carbonization process is carried out in an argon environment, the carbonization temperature is 600-800°C, the heating rate is 5°C / min, and the insulation time is 2h.

[0021] Preferably, in step S4, the mass ratio of sublimated sulfur to carbonized fiber membrane used in vapor phase vulcanization is 10:1, the vulcanization environment is argon atmosphere, the vulcanization temperature is 500° C., the holding time is 2 h, and the heating rate is 5° C. / min.

[0022] Preferably, in step S5, the thickness of the battery positive electrode material cut to be obtained is 120-130 μm.

[0023] Therefore, the present invention adopts the above-mentioned method for preparing a self-supporting positive electrode of iron disulfide electrospinning for aqueous batteries, which has the following beneficial effects:

[0024] 1. The present invention designs and prepares a continuous three-dimensional network structure through an electrospinning process. Through subsequent continuous heat treatment, the porous carbon fiber matrix constructed in situ well disperses and connects the nano-iron disulfide particles. The unique structural design and nitrogen atom doping improve the intrinsic defect level of the carbon material while accelerating the electron transfer rate, forming an efficient three-dimensional conductive network, which is beneficial to the transmission and diffusion of electrons and ions;

[0025] 2. The unique three-dimensional structure prepared by the present invention can effectively inhibit the volume expansion, dissolution loss of active materials and agglomeration of discharge products during the reaction process, thereby improving the electrochemical stability and cycle life of the positive electrode material;

[0026] 3. The design of the self-supporting positive electrode provided by the present invention can avoid the use of current collectors, binders and conductive agents, greatly improve the mass energy density of the positive electrode, and the process of combining electrospinning and in-situ heat treatment is convenient for industrial production and commercial application; the preparation method of the present invention can realize the preparation of positive electrode self-supporting materials with excellent rate performance and cycle performance;

[0027] 4. The iron disulfide electrospun self-supporting positive electrode prepared by the present invention is applied to the aqueous battery system. Compared with the commonly used lithium batteries nowadays, the aqueous battery has the characteristics of intrinsic safety and low cost. The conversion reaction of FeS2 based on multi-electron transfer can show a higher specific capacity, which can effectively make up for the disadvantage of low capacity of aqueous batteries. The positive electrode material of this work not only shows self-supporting characteristics and high specific capacity, but also can maintain long-term cycle stability under high current conditions, has good rate performance and service life, and shows advancedness.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a preparation flow chart of a method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries;

[0030] Figure 2 This is the XRD pattern of the sample prepared in Example 1 of the present invention;

[0031] Figure 3 This is the SEM scanning spectrum of the sample prepared in Example 1 of the present invention;

[0032] Figure 4 This is an optical photograph of a sample prepared in Example 1 of the present invention;

[0033] Figure 5 The interface thickness of the sample prepared in Example 1 of the present invention;

[0034] Figure 6 This is a high current long cycle test diagram of the sample prepared in Example 1 of the present invention and applied in an aqueous copper ion battery;

[0035] Figure 7 This is a rate performance test diagram of the sample prepared in Example 1 of the present invention and applied in an aqueous copper ion battery.

[0036] Figure 8 The XRD pattern of the synthetic sample prepared in Example 2 of the present invention;

[0037] Fig. 9 This is the XRD pattern of the synthetic sample prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0039] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0040] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0041] like Figure 1As shown in the preparation flow chart, the present invention provides a method for preparing an electrospinning self-supporting positive electrode of iron disulfide for an aqueous battery, comprising the following steps:

[0042] S1, adding polyacrylonitrile (PAN) and ferric acetate into N, N-dimethylformamide (DMF), stirring evenly until completely dissolved to form a uniform spinning solution;

[0043] S2, transferring the spinning solution into a syringe, applying high voltage between the needle of the syringe and the collector, and spinning the nanofiber membrane in situ on the collector by controlling the injection speed and the rotation speed of the drum;

[0044] S3, after drying the nanofiber membrane, annealing at low temperature in air to stabilize it, dehydrogenation, cyclization and oxidation of polyacrylonitrile (PAN) occurs, Fe(AC)2 is oxidized to Fe2O3, and the nanofiber membrane is further carbonized, Fe2O3 is converted to Fe3C, and at the same time, due to the pyrolysis of the additional nitrile group, the carbon content increases, and finally a carbonized fiber membrane rich in pore structure is obtained. The carbonized fiber membrane is a three-dimensional porous material, and this structure greatly improves the electrolyte infiltration degree and active specific surface area;

[0045] S4. The carbonized fiber membrane is subjected to vapor phase sulfurization, and the iron carbide is converted into iron disulfide nanoparticles in situ. The Fe3C embedded in the nanocarbon fiber reacts with the sulfur-containing atmosphere at high temperature and is converted into FeS2 nanoparticles in situ, which are evenly distributed on the porous three-dimensional carbon fiber skeleton of the carbonized fiber membrane to obtain a nanofiber film loaded with iron disulfide; a high-speed electron and ion transmission channel is constructed, which inhibits the structural damage of the positive electrode due to volume expansion during the reaction and improves the structural stability of the positive electrode material;

[0046] S5. The nanofiber film loaded with iron disulfide is used as a positive electrode material for a battery by cutting.

[0047] The mass ratio of the nanofiber film to the loaded iron disulfide is 1:3-4.

[0048] In step S1, the molecular weight of polyacrylonitrile is 150000-200000, the input mass ratio of polyacrylonitrile and ferric acetate is 7:8, the mass volume ratio of ferric acetate to dimethylformamide is 0.8g:8-10ml, and the stirring time is 12h.

[0049] In step S2, the diameter of the syringe needle is 19-21G, the distance between the syringe needle and the collector is fixed at 18cm, the negative high voltage and positive high voltage are -2 and 16kV respectively, the injection speed is 1ml / h, the drum speed is 200r / min, and the spinning environment humidity is controlled at 25-35%.

[0050] In step S3, the stable temperature of low-temperature annealing in air is 280°C, the heating rate is 2°C / min, and the holding time is 2h. The carbonization process is carried out in an argon environment, the carbonization temperature is 600-800°C, the heating rate is 5°C / min, and the holding time is 2h.

[0051] In step S4, the mass ratio of sublimated sulfur to carbonized fiber membrane in vapor phase vulcanization is 10:1, the vulcanization environment is argon atmosphere, the vulcanization temperature is 500° C., the holding time is 2 h, and the heating rate is 5° C. / min.

[0052] In step S5, the thickness of the battery positive electrode material cut to be 120-130 μm.

[0053] Example 1

[0054] S1. Weigh 0.7 g of polyacrylonitrile (PAN, Mw=150000) and 0.8 g of ferric acetate and add them into 8 ml of N,N-dimethylformamide (DMF). Continue stirring until dissolved to form a uniform spinning solution.

[0055] S2, the spinning solution was transferred into a 10 ml syringe with a needle of 21G, placed on a syringe pump, the injection speed was 1 ml / h, high voltage was applied between the syringe needle and the collector, wherein the negative voltage and the positive voltage were -2 and 16 KV respectively, the distance between the syringe needle and the collector was fixed at 18 cm, and the nanofiber membrane was spun in situ on the collector by controlling the injection speed to 1 ml / h and the drum speed to 200 r / min;

[0056] S3, pre-oxidizing the synthesized nanofiber membrane at 280 °C for 2 h at 2 °C / min, and then carbonizing at 700 °C for 2 h at 5 °C / min in an argon environment;

[0057] S4. Place the carbonized fiber membrane and sublimated sulfur in the downstream and upstream of the tubular furnace respectively at a mass ratio of 1:10, and sulfurize them at 500°C for 2 hours at 5°C / min in an argon atmosphere. After cooling, cut them to obtain the final product - iron disulfide electrospun self-supporting positive electrode.

[0058] The XRD pattern of the final sample prepared and synthesized in this example is as follows Figure 2 As shown, the results show that this embodiment contains pure FeS2 and no impurities.

[0059] At the same time, through Figure 3 It can be seen from the SEM scanning spectrum that the average diameter of the fiber prepared in this embodiment is 400nm, and the fiber is rich in porous structure, which greatly improves the active specific surface area of ​​the positive electrode structure and increases the wettability of the electrolyte.

[0060] Figure 4This is an optical photograph of the iron disulfide electrospun self-supporting positive electrode prepared in this example. It can be seen from the figure that the iron disulfide electrospun self-supporting positive electrode synthesized by the invention exhibits good mechanical flexibility and Figure 5 The results in the study show that the thickness of the sample is 127 μm, which supports its application in flexible devices.

[0061] Finally, the electrospun self-supporting positive electrode of iron disulfide prepared in this example was applied to an aqueous copper ion battery, and its electrochemical performance was tested. The test results are as follows: Figure 6 as well as Figure 7 As shown, after 4000 cycles at a current density of 5A / g, the specific capacity can still be maintained at 385mAh / g, and the capacity retention rate is above 85%, showing good cycle performance. At the same time, the specific capacity of 387mAh / g can be achieved at a current density of 15A / g, showing excellent rate performance.

[0062] Example 2

[0063] S1. Weigh 0.7 g of polyacrylonitrile (PAN, Mw=150000) and 0.8 g of ferric acetate and add them into 8 ml of N,N-dimethylformamide (DMF). Continue stirring until dissolved to form a uniform spinning solution.

[0064] S2, the spinning solution was transferred into a 10 ml syringe with a needle of 21G, placed on a syringe pump, the injection speed was 1 ml / h, high voltage was applied between the syringe needle and the collector, wherein the negative voltage and the positive voltage were -2 and 16 KV respectively, the distance between the syringe needle and the collector was fixed at 18 cm, and the nanofiber membrane was spun in situ on the collector by controlling the injection speed to 1 ml / h and the drum speed to 200 r / min;

[0065] S3, pre-oxidizing the synthesized nanofiber membrane at 280 °C for 2 h at 2 °C / min, and then carbonizing at 600 °C for 2 h at 5 °C / min in an argon environment;

[0066] S4. Place the carbonized fiber membrane and sublimated sulfur in the downstream and upstream of the tubular furnace respectively at a mass ratio of 1:10, and sulfurize them at 500°C for 2 hours at 5°C / min in an argon atmosphere. After cooling, cut them to obtain the final product - iron disulfide electrospun self-supporting positive electrode.

[0067] The XRD pattern of the final sample prepared and synthesized in this example is as follows Figure 8 As shown, the results show that this embodiment contains pure FeS2 and no impurities.

[0068] Example 3

[0069] S1. Weigh 0.7 g of polyacrylonitrile (PAN, Mw=150000) and 0.8 g of ferric acetate and add them into 8 ml of N,N-dimethylformamide (DMF). Continue stirring until dissolved to form a uniform spinning solution.

[0070] S2, the spinning solution was transferred into a 10 ml syringe with a needle of 21G, placed on a syringe pump, the injection speed was 1 ml / h, high voltage was applied between the syringe needle and the collector, wherein the negative voltage and the positive voltage were -2 and 16 KV respectively, the distance between the syringe needle and the collector was fixed at 18 cm, and the nanofiber membrane was spun in situ on the collector by controlling the injection speed to 1 ml / h and the drum speed to 200 r / min;

[0071] S3, pre-oxidizing the synthesized nanofiber membrane at 280 °C for 2 h at 2 °C / min, and then carbonizing at 800 °C for 2 h at 5 °C / min in an argon environment;

[0072] S4. Place the carbonized fiber membrane and sublimated sulfur in the downstream and upstream of the tubular furnace respectively at a mass ratio of 1:10, and sulfurize them at 500°C for 2 hours at 5°C / min in an argon atmosphere. After cooling, cut them to obtain the final product - iron disulfide electrospun self-supporting positive electrode.

[0073] The XRD pattern of the final sample prepared and synthesized in this example is as follows Fig. 9 As shown, the results show that this embodiment contains pure FeS2 and no impurities.

[0074] Therefore, the present invention adopts the above-mentioned method for preparing the electrostatic spinning self-supporting positive electrode of iron disulfide for aqueous batteries. The preparation method uses electrostatic spinning technology, and after low-temperature stabilization and high-temperature carbonization, a three-dimensional mesh carbon fiber composite material is designed and prepared, and nano iron disulfide particles are obtained by in-situ sulfurization on the basis of the material. Finally, the prepared iron disulfide / nitrogen-doped carbon fiber self-supporting positive electrode shows excellent rate performance and cycle performance. At the same time, since the use of current collectors, binders and conductive agents is avoided, the mass energy density of the battery is greatly improved, showing good application prospects.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries, characterized in that: The following steps are involved: S1, adding polyacrylonitrile and ferric acetate into N,N-dimethylformamide, stirring evenly until completely dissolved to form a uniform spinning solution; S2, transferring the spinning solution into a syringe, applying high voltage between the needle of the syringe and the collector, and spinning the nanofiber membrane in situ on the collector by controlling the injection speed and the rotation speed of the drum; S3, after drying the nanofiber membrane, annealing at low temperature in air to stabilize it, converting iron acetate into iron oxide, and then carbonizing the nanofiber membrane to convert iron oxide into iron carbide, thereby obtaining a carbonized fiber membrane with a rich porous structure; S4, subjecting the carbonized fiber membrane to gas phase vulcanization, converting the iron carbide into iron disulfide nanoparticles in situ, and obtaining a nanofiber film loaded with iron disulfide; S5. Cut the nanofiber film loaded with iron disulfide and use it as the positive electrode material of the battery.

2. The method for preparing a self-supporting positive electrode of an aqueous battery by electrospinning of iron disulfide according to claim 1, characterized in that: The mass ratio of the nanofiber film to the loaded iron disulfide is 1:3-4.

3. The method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries according to claim 1, characterized in that: In step S1, the molecular weight of polyacrylonitrile is 150000-200000, the input mass ratio of polyacrylonitrile and ferric acetate is 7:8, the mass volume ratio of ferric acetate to dimethylformamide is 0.8g:8-10ml, and the stirring time is 12h.

4. The method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries according to claim 1, characterized in that: In step S2, the diameter of the syringe needle is 19-21G, the distance between the syringe needle and the collector is fixed at 18cm, the negative high voltage and positive high voltage are -2 and 16kV respectively, the injection speed is 1ml / h, the drum speed is 200r / min, and the spinning environment humidity is controlled at 25-35%.

5. The method for preparing a self-supporting positive electrode of electrospun iron disulfide for aqueous batteries according to claim 1, characterized in that: In step S3, the stable temperature of low-temperature annealing in air is 280°C, the heating rate is 2°C / min, and the holding time is 2h.

6. The method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries according to claim 1, characterized in that: In step S3, the carbonization process is carried out in an argon environment, the carbonization temperature is 600-800°C, the heating rate is 5°C / min, and the insulation time is 2h.

7. The method for preparing a self-supporting positive electrode of iron disulfide electrospun for aqueous batteries according to claim 1, characterized in that: In step S4, the mass ratio of sublimated sulfur to carbonized fiber membrane in vapor phase vulcanization is 10:1, the vulcanization environment is argon atmosphere, the vulcanization temperature is 500° C., the holding time is 2 h, and the heating rate is 5° C. / min.

8. The method for preparing a self-supporting positive electrode of electrospun iron disulfide for aqueous batteries according to claim 1, characterized in that: In step S5, the thickness of the battery positive electrode material cut to be 120-130 μm.

Citation Information

Patent Citations

  • Lithium-sulfur battery self-supporting cathode material and electro-spinning preparation method thereof

    CN110438798A

  • Flexible self-supporting vanadium heptacarbide / nitrogen-doped porous carbon nanofiber composite material as well as preparation method and application of flexible self-supporting vanadium heptacarbide / nitrogen-doped porous carbon nanofiber composite material

    CN116111064A

  • Flexible self-supporting lithium-sulfur battery composite positive electrode material and preparation method thereof

    CN116487558A